Perilaku Aparatur Pemerintah Dalam Pelaksanaan Tugas Pokok dan Fungsi Pada Biro Pembangunan Sekretariat Daerah Provinsi Sulawesi Utara - Wongkar, Anita; Rumapea, Patar; Liando, Daud (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this study is to assess and describe the behavior of government officials in the implementation of basic tasks and functions of the Secretariat of the Regional Development Agency of North Sulawesi Province. The method used is a qualitative research method. Data collected through direct interviews. The results showed: (1) The behavior of labor discipline an employee-owned Development Bureau Regional Secretariat of North Sulawesi province has not been fully realized well in the execution of duties; (2) Conduct employee morale Development Bureau Secretariat of North Sulawesi Province has not been fully optimized in the execution of duties; (3) Not yet fully optimal coordination of the behavior of employees in the execution of duties. Keywords: Behavior, Discipline, Spirit, Coordination